Analisis Hasil Evaluasi Pengetahuan PHBS dan Tren Kasus Scabies di Pondok Pesantren Al Ishlah Kecamatan Natar - Anggi Dhea Mirza; Helina Helmy; Agus Sutopo; Haris Kadarusman (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2024)
Scabies cases in the working area of the Sukadamai Inpatient Health Center look quite high, with numbers from 24 cases to 107 cases until December 2023. This shows that Scabies is still a significant health problem among students in Islamic boarding schools. PHBS (Clean and Healthy Living Behavior) refers to the practice of maintaining cleanliness and healthy living habits in daily life. This is an important aspect in preventing the spread of diseases, including Scabies. Good knowledge of PHBS can reduce the risk of Scabies in Islamic boarding schools. The purpose of analyzing the results of the evaluation of PHBS knowledge and trends in Scabies cases in Islamic boarding schools is to find out to help identify obstacles and obstacles that stand in the way of preventing and transmitting the incidence of Scabies disease in students in Islamic boarding schools and identifying how PHBS knowledge affects the possibility of Scabies among students. Observation and documentation were the methods used to collect data for this study. From the observations, it was found that before counseling, students' knowledge was limited, but after counseling, students' knowledge became good and understood about Scabies disease and its prevention. Scabies counseling in Islamic boarding schools has a significant impact in increasing students' awareness, knowledge, and behavior about Scabies, as well as helping to reduce the incidence and treatment of Scabies among students